COVID-19, Time to Change Course - Olen R Brown (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2021)
Nearly one year ago the world awoke to a new disease, COVID-19. National economies and the lives of almost every individual on the planet Earth were directly impacted. The initial political and medical successes were to "flatten the curve" with social distancing, wearing masks and "lock-down" of society, and then to race toward a safe and effective vaccine. Two vaccines have now been developed and approved in the United States and one in England.